2020
DOI: 10.1038/s41366-020-0609-4
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of prenatal maternal obesity and diabetes to offspring neurodevelopmental and psychiatric disorders: a narrative review

Abstract: Obesity and diabetes is a worldwide public health problem among women of reproductive age. This narrative review highlights recent epidemiological studies regarding associations of maternal obesity and diabetes with neurodevelopmental and psychiatric disorders in offspring, and provides an overview of plausible underlying mechanisms and challenges for future human studies. A comprehensive search strategy selected terms that corresponded to the domains of interest (maternal obesity, different types of diabetes,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
51
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(65 citation statements)
references
References 176 publications
2
51
0
Order By: Relevance
“…The detrimental effects of poor maternal diet and maternal diet-induced obesity on offspring development are well established [ 46 , 47 , 48 ], as is the role that maternal diet plays in disrupting the maturation of hypothalamic satiety signalling [ 13 ]. The poor neurodevelopmental consequences of maternal obesity have been attributed in part to insufficient intake of ω3 fatty acids [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…The detrimental effects of poor maternal diet and maternal diet-induced obesity on offspring development are well established [ 46 , 47 , 48 ], as is the role that maternal diet plays in disrupting the maturation of hypothalamic satiety signalling [ 13 ]. The poor neurodevelopmental consequences of maternal obesity have been attributed in part to insufficient intake of ω3 fatty acids [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…While maternal obesity has long been known to pose increased cardiometabolic risk for offspring, reviews and meta-analyses over the past decade have focused on the impacts of maternal obesity on offspring behaviour and cognition [ 5 , 50 ]. For instance, in a study of 1361 mother-child pairs (Project Viva cohort), Monthe-Dreze et al [ 20 ] found that higher pre-pregnancy BMI (>30) was associated with poorer visual motor abilities at three years of age, with this relationship partly mediated by maternal inflammation (dietary inflammatory index and n−6:n−3 PUFA ratio).…”
Section: Cognitive and Behavioural Effects Of Maternal Obesity/matermentioning
confidence: 99%
“…The potential link between maternal obesity and Autism Spectrum Disorder (ASD) has been extensively investigated over the past decade or so. Several recent meta-analyses and reviews indicate an increased risk of ASD in children of mothers who were overweight or obese at the time of conception [ 6 , 50 ]. In addition, several studies have examined the impact of maternal obesity on psychosocial development, regulatory behaviour, internalising and externalising behaviour.…”
Section: Cognitive and Behavioural Effects Of Maternal Obesity/matermentioning
confidence: 99%
“…More specifically, maternal obesity was linked to reduction in child intelligence quotient (IQ) scores (Neggers et al, 2003;Gage et al, 2013;Bliddal et al, 2014;Pugh et al, 2015), cognitive test scores (Tanda et al, 2013), impaired neuropsychological development (Hinkle et al, 2012;Casas et al, 2013;Huang et al, 2014) and autism spectrum disorder and other intellectual disabilities (Brion et al, 2011;Li et al, 2016;Kong et al, 2020) in the children. Additionally, other studies suggested that an association might exist between maternal obesity and increased symptoms of attention-deficit hyperactivity disorder (ADHD) in children (Rodriguez et al, 2008;Rodriguez, 2010;Buss et al, 2012;Jenabi et al, 2019;Kong et al, 2020;Robinson et al, 2020). Although the association between maternal obesity and offspring's cognitive disabilities was described, the current literature is still scarce, and findings are inconsistent (Brion et al, 2011;Keim and Pruitt, 2012;Van Lieshout, 2013;Bliddal et al, 2014).…”
Section: The Long Term-effects Of Maternal Overnutrition On Cognitivementioning
confidence: 99%